Temperature shift of intraband absorption peak in tunnel-coupled QW structure (2017)
An experimental study of the intersubband light absorption by the 100-period GaAs/Al0.25Ga0.75As double quantum well heterostructure doped with silicon is reported and interpreted. Small temperature redshift of the 1–3 intersubband absorption peak is detected. Numerical calculations of the absorption coefficient including self-consistent Hartree calculations of the bottom of the conduction band show good agreement with the observed phenomena. The temperature dependence of energy gap of the material and the depolarization shift should be accounted for to explain the shift. © 2017 Elsevier B.V.